The Effect of Leadership Style, Organizational Culture and Compensation on Employee Performance Through Work Motivation as an Intervening Variable (Study At PT. Tiki Jalur Nugaraha Ekakurir Bandung) - Dea Ade Roslina; Anton Budi Santoso (Dinasti Review, 2025)
Service industry players are currently always required to provide faster services to meet market demand and avoid losing market share or customers. This study aims to examine the effect of leadership style, organizational culture, and compensation on employee performance through work motivation as an intervening variable at PT Tiki Jalur Nugraha Ekakurir. In this study, the author uses descriptive and verification methods with a survey approach, which involves collecting data through questionnaires from population samples to analyze the relationship between variables. Descriptive research aims to describe variables without comparing or relating them to other variables, while verification research aims to test theories and produce new scientific information through hypothesis testing, using questionnaires to collect data from a sample of 186 employees selected by accident. Data analysis was carried out using a structural equation model (SEM) to test the relationship between variables. The results of the study revealed that there was a significant effect of leadership style on employee performance. However, no significant effect was found between organizational culture and employee performance. There was a significant effect of compensation on employee performance. In addition, leadership style, organizational culture, and compensation also affect work motivation. Work motivation has been shown to have a positive effect on employee performance. In addition, the results of this study also show that leadership style, organizational culture, and compensation have an influence on employee performance through work motivation as an intervening variable.